Different VO2max time-averaging intervals in swimming - Fernandes, R. J.; de Jesus, K.; Baldari, C.; de Jesus, K.; Sousa, A. C.; Vilas-Boas, J. P.; Guidetti, L. (International Journal of Sports Medicine, 2012)
We aimed to determine the effect of sampling interval strategy on VO2max assessment to establish a standard time averaging method that allows a better identification of the VO2 plateau incidence in swimming. To this end, 3 incremental protocols utilizing different step lengths for each sampling interval were used to compare VO2max measurements. 11 trained male swimmers performed 3 repetitions of a front crawl intermittent incremental protocol until exhaustion (increments of 0.05 m.s - 1, with 30 s and 24-48 h intervals between steps and tests, respectively) with 200, 300 and 400-m step lengths. VO2 was directly measured, and 6 sampling intervals were compared: bxb and averages of 5, 10, 15, 20 and 30 s. Shorter sampling intervals (=15 s) allowed the highest incidence of the VO2 plateau, independent of the step lengths used; the 200 and 300-m step protocols accounted for higher percentage of V?O2 plateau incidence, and higher VO2max values, compared to the 400-m step protocol. As an optimal sampling interval should be used for the validation of the research findings, and considering that swimmers and coaches prefer less time-consuming protocols, the use of the 10 s time-average interval (once bxb and 5 s samplings present high variability) in a 200-m step incremental protocol for VO2max assessment in swimming is suggested.